Fri0611 english language proficiency and total knee/hip replacement outcomes: is there a relationship?. (12th June 2018) - Mehta, B.; Szymonifka, J.; Dey, S. A.; Navarro-Millan, I. Y.; Grassia, S. V.; Mandl, L. A.; Bass, A. R.; Russell, L. A.; Parks, M. L.; Figgie, M. P.; Lee, Y.-Y.; Nguyen, J. T.; et al.
Abstract : Background: Health care disparities are recognized for medical and surgical outcomes in patients with Limited English Proficiency (LEP) (1). Objectives: The purpose of this study is to assess the association of LEP on Total Knee Replacement (TKR) and Total Hip Replacement (THR) outcomes. Methods: Individual patient-level variables were obtained from a single institution TKR and THR registry between 5/1/07 and 2/1/11. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and function scores at baseline and 2 years after elective TKR and THR were collected and retrospectively analyzed. We used census tract LEP-"Less than very well" as recommended for screening individuals, since individual LEP data is not collected in most cohorts, We obtained census level data using patients' geocodable addresses (2). Only patients from closest states (NY, NJ and CT) were included. Data was analyzed using univariate and multivariable linear mixed effects models, with census tracts variables treated as random effects. Results: Table 1 describes the characteristics of the patients with THR n=4009) and TKR(n=3898). In univariable analyses, for every percent increase in LEP, the WOMAC scores at baseline and 2 year were universally decreased and are statistically significant (p value <0.001). However in the multivariable model when adjusted for neighborhood poverty age, BMI, sex, comorbidities, and the Gini coefficient these changes were not statistically significant, suggesting potential confounders (table 2). While women had worse baseline and 2-year WOMAC pain and function scores (all p≤0.04), this difference was not significantly influenced by neighborhood LEP (all pinteraction NS). Methodology: : Categorical variables are summarized as frequency (percent). Continuous variables are summarized as mean <??> standard deviation Methodology: : Univariate and multivariable linear mixed-effects models were analyzed, with census tracts treated as random effects. In addition to neighborhood Limited English Proficiency; variables included in the model were; age, BMI, sex, ≥ 1 comorbidity; neighborhood percent poverty (<10%, 10% – < 20%, 20% – < 30%, 30% – < 40%, ≥ 40% [reference group]), neighborhood Gini coefficient was also included. Conclusions: Patients coming from neighborhoods with lower english proficiency have worse pain and function scores in unadjusted models. However when adjusted for potential confounders, the difference is not significant. Community factors which contribute to healthcare disparities are multidimensional, prospective studies collecting individual LEP data would be warranted to study this aspect in detail. References: [1] John-Baptiste A, et al. The effect of English language proficiency on length of stay and in-hospital mortality. J Gen Intern Med2004. [2] Karliner LS, et al. Identification of limited English proficient patients in clinical care. J Gen Intern Med2008. Disclosure of Interest: B. Mehta: None declared, J. Szymonifka: None declared, S. Dey: None declared, I. Navarro-Millan: None declared, S. Grassia: None declared, L. Mandl Grant/research support from: Boehringer-Ingelheim, A. Bass Grant/research support from: Abbott, Pfizer, L. Russell: None declared, M. Parks Grant/research support from: Zimmer, Consultant for: Zimmer, M. Figgie Shareholder of: Mekanika, Y.-Y. Lee: None declared, J. Nguyen: None declared, S. Goodman: None declared